Contribution to the knowledge of Podischnus Burmeister, 1847 (Coleoptera, Melolonthidae: Dynastinae) with the description of two new species from Brazilian Amazon Forest - Duarte, Paulo Roberto Marinho; Grossi, Paschoal Coelho (Papéis Avulsos de Zoologia, 2020)
Two new Podischnus Burmeister, 1847 species are described here: Podischnus limeirai sp. nov. from Gurupi region, Maranhão state, Brazil, the easternmost distribution of the genus; and Podischnus cleidecostae sp. nov. from the Acre state, Western of Brazilian Amazon Forest. New diagnostic characters are illustrated and discussed for the genus. An illustrated identification key for all Podischnus species, and an up-to-date distribution map for the Brazilian species of Podischnus are provided. Moreover, we propose the inclusion of P. limeirai sp. nov. in the Red List of Threatened Species (IUCN) due to the fast loss of the Oriental Amazon Forest remnant fragment in that region.